Ownership Structure and Board Characteristics as Determinants of CEO Turnover in South African JSE Listed Companies - Mofokeng, Rethabile Thandolwethu (Department of Finance and Tax, 2021)
The CEO of a large listed firm is often under public scrutiny due to listing requirements of stock exchanges of the respective country as well as pressures from stakeholders. Of these stakeholders, shareholders are mostly interested in the firm performance as it relates to their investment to determine if their investment is still worthwhile as well as to determine its returns. A CEO has the duty of ensuring that a firm meets its set targets and the responsibility of having to account for any deviations from these targets. In a firm with sound corporate governance measures, any underperformance experienced by the firm should result in the CEO being replaced and when targets met, the CEO being rewarded. However this is not always the case and this study considers the key determinants of CEO turnover as it later aims to determine what these key determinants are in South African JSE-listed firms as well as the correlation with CEO turnover. This study examines the relationship between ownership structure and board characteristics on CEO-firm performance sensitivity. The population for this study was 60 companies listed on the Johannesburg Stock Exchange. The period covered for this study runs over 5 years from 2013 to 2017. This period was chosen mainly because data for some companies was missing for the period beyond 2017. Thus, excluding companies that had no data for the period beyond 2017 could have reduced the sample further and would have made the analysis less meaningful. The study reports three important findings. The first is that CEO turnover is insensitive to firm performance, irrespective of whether it is an accounting-based firm performance (i.e CEO turnover vs EBIT/Assets ratio) or market-based measure of firm performance (lagged stock returns, 18, 24, and 36 months respectively). Second, the findings of this study show that CEO age and institutional ownership are inversely related to CEO turnover. In addition, board size becomes a significant determinant of CEO turnover when the model in includes returns lagged over 36 months or when the EBIT/Assets ratio is part of the Model (see models 7 and 8), although this is only at 10% level of significance. Third, board insiders and firm size are found to be unrelated to CEO turnover.